Search
Ask a question
0

(sin^6 x)/(1- tan^2 x) + (cos^6 x)/(1- cot^2 x)

simplify simplify simplify simplify ...............

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Robert J. | Certified High School AP Calculus and Physics TeacherCertified High School AP Calculus and Ph...
4.6 4.6 (13 lesson ratings) (13)
0
Check Marked as Best Answer
 
(sin^6 x)/(1-tan^2 x) + (cos^6 x)/(1-cot^2 x)
= sin^6 x/(1 - sin^2 x/cos^2 x) + cos^6 x/(1 - cos^2 x/sin^2 x)
= sin^6 x cos^2 x/(cos^2 x - sin^2 x) + cos^6 x sin^2 x/(sin^2 x - cos^2 x)
= sin^2 x cos^2 x (sin^4 x - cos^4 x)/(cos^2 x - sin^2 x)
= sin^2 x cos^2 x (sin^2 x - cos^2 x)(sin^2 x + cos^2 x)/(cos^2 x - sin^2 x)
= -sin^2 x cos^2 x <==Answer
-------
Attn:
sin^2 x + cos^2 x = 1